Paramecium BBS genes are key to presence of channels in Cilia - Valentine, Megan Smith (BioMed Central, 2012)
BACKGROUND: Changes in genes coding for ciliary proteins contribute to complex human syndromes called ciliopathies, such as Bardet-Biedl Syndrome (BBS). We used the model organism Paramecium to focus on ciliary ion channels that affect the beat form and sensory function of motile cilia and evaluate the effects of perturbing BBS proteins on these channels. METHODS: We used immunoprecipitations and mass spectrometry to explore whether Paramecium proteins interact as in mammalian cells. We used RNA interference (RNAi) and swimming behavior assays to examine the effects of BBS depletion on ciliary ion channels that control ciliary beating. Combining RNA interference and epitope tagging, we examined the effects of BBS depletion of BBS 7, 8 and 9 on the location of three channels and a chemoreceptor in cilia. RESULTS: We found 10 orthologs of 8 BBS genes in P. tetraurelia. BBS1, 2, 4, 5, 7, 8 and 9 co-immunoprecipitate. While RNAi reduction of BBS 7 and 9 gene products caused loss and shortening of cilia, RNAi for all BBS genes except BBS2 affected patterns of ciliary motility that are governed by ciliary ion channels. Swimming behavior assays pointed to loss of ciliary K(+) channel function. Combining RNAi and epitope tagged ciliary proteins we demonstrated that a calcium activated K(+) channel was no longer located in the cilia upon depletion of BBS 7, 8 or 9, consistent with the cells’ swimming behavior. The TRPP channel PKD2 was also lost from the cilia. In contrast, the ciliary voltage gated calcium channel was unaffected by BBS depletion, consistent with behavioral assays. The ciliary location of a chemoreceptor for folate was similarly unperturbed by the depletion of BBS 7, 8 or 9. CONCLUSIONS: The co-immunoprecipitation of BBS 1,2,4,5,7,8, and 9 suggests a complex of BBS proteins. RNAi for BBS 7, 8 or 9 gene products causes the selective loss of K(+) and PKD2 channels from the cilia while the critical voltage gated calcium channel and a peripheral receptor protein remain undisturbed. These channels govern ciliary beating and sensory function. Importantly, in P. tetraurelia we can combine studies of ciliopathy protein function with behavior and location and control of ciliary channels.